Slope Assessment Systems: A Review and Evaluation of Current Techniques Used for Cut Slopes in the Mountainous Terrain of West Malaysia - Harwant Singh; Kim Huat, Bujang; Jamaludin, Suhaimi (Electronic Journal of Geotechnical Engineering, 2008)
In Malaysia, slope assessment systems (SAS) are widely used in assessing the instability of slopes or the probability of occurrence and likely severity of landslides. These SAS can be derived based on either one particular approach or combination of several approaches of landslide assessments and prediction. This paper overviews five slope assessment systems (SAS) developed in Malaysia for predicting landslide for large-scale assessments. They are the Slope Maintenance System (SMS), Slope Priority Ranking System (SPRS), Slope Information Management System (SIMS), the Slope Management and Risk Tracking System (SMART), and the Landslide Hazard and Risk Assessment (LHRA). An attempt is made to evaluate the accuracy of these SAS in predicting landslides based on slope inventory data from 139 cut slopes in granitic formations, and 47 cut slopes in meta-sediment formations, which are the two most common rock/soil formations found in West Malaysia. Based on this study, it was found that none of the existing SAS is satisfactory for predicting landslides of cut slopes in granitic formations, for various reasons such as the use of a hazard score developed from another country, an insufficient data base, an oversimplified approach, and the use of data base derived from different rock/soil formations. However for the case of cut slopes in meta-sediment, the Slope Management and Risk Tracking System (SMART) was found to be satisfactory with a 90% prediction accuracy. The current database of SMART is largely based on meta-sediment formations from the Kundusang area of Sabah, East Malaysia.